Distance Learning: Kreatifitas Guru dalam Melaksanakan PJJ Masa Pandemi COVID-19 pada MI Hayatul Islamiyah & SD Islam Kamila Insan Cita - Rosfiani, Okta; Kirana, Andi Ade Diandra; Al-Iklatussolehah, Dwi Putri; Al-Kafi, Muhammad Caesar (TSAQOFAH, 2025)
This case study aims to examine teachers' abilities in implementing distance learning in PAI subjects during the COVID-19 pandemic. To find out more about the ability of teachers at MI Hayatul Islamiyah Cinangka and SD Islam Kamila Insan Cita in implementing distance learning during the COVID-19 pandemic is the aim of this research. The Narrative Method is a qualitative approach used in this research. Online classroom observations, in-depth interviews with teachers, and examination of teaching materials were used to collect data. The findings of this study indicate that educators have difficulty managing time, providing constructive criticism, and keeping students engaged. However, educators are also showing ingenuity by utilizing various digital resources to improve teaching. To help teachers implement distance learning successfully, this research concludes that professional development centered on improving pedagogical and technological skills is essential.